A Systematic Literature Review: Medical Relevance and Ethical Implications of Color Blindness Requirements for Medical School Candidates - Narumi Hayakawa (Journal of Social Research, 2026)
This study addresses the ongoing debate regarding the medical relevance and ethical implications of color vision deficiency (CVD) requirements for medical school admission. Traditionally, many medical institutions require candidates to be free from color blindness based on the assumption that accurate color perception is essential for diagnosing clinical signs such as cyanosis, jaundice, and skin lesions. However, the rapid development of medical technology and diagnostic tools has raised questions about whether such requirements remain justified. Therefore, this study aims to evaluate the medical relevance of color vision requirements and examine their ethical implications in the context of modern medical education. This research employs a systematic literature review method by analyzing peer-reviewed articles published between 2020 and 2025. Relevant studies were collected from major scientific databases, including PubMed, Scopus, Web of Science, ProQuest, and Google Scholar. The selected articles were screened using predefined inclusion and exclusion criteria, followed by quality assessment and thematic synthesis to identify patterns related to clinical competence, technological adaptation, and ethical considerations. The findings show that the prevalence of color vision deficiency among medical students ranges from approximately 1.4% to 6%; however, direct evidence linking CVD to significant clinical errors remains limited. Advances in digital diagnostic tools and assistive technologies also enable individuals with CVD to compensate effectively in clinical practice. From an ethical perspective, strict exclusion policies may raise concerns regarding fairness and equal access to medical education. In conclusion, the study suggests that, rather than absolute exclusion, a more inclusive and evidence-based approach—such as early screening, adaptive training, and specialization guidance—should be considered to balance patient safety with equitable access to the medical profession.